THE INFLUENCE OF THE ENVIRONMENT ON MISPRONUNCIATION OF ENGLISH COMMON WORDS IN INDONESIA (CASE STUDY) - Yanuarius Yanu Darmawan; Immaniar Immaniar; Layalia Faza (Universitas Bandar Lampung, 2019)
English becomes a very important language in Indonesia. Everyone seems to be obliged to learn English even more so this language has become a compulsory curriculum in school. The influence of the use of English can be up to the use of new words that seem difficult to replace with the Indonesian language. Because English pronunciation is more complicated than Indonesian pronunciation, the Indonesians are hard to pronounce exactly as the original. This different pronunciation is already wrong but has become a common pronunciation dictionary. Every pronunciation that comes from variety of backgrounds and those backgrounds really decide how good a person listen and say standard pronunciation of English.